Shadow Puppets [compact disc, unabridged] - Card, Orson Scott (Card, Orson Scott. Shadow saga., 2002)
After Ender Wiggin's triumph over the Formics, society has been altered by the destruction of unity between the nations, but Ender's older brother is determined to restore Earth's unity with the help of the warriors from the Battle School.